Characterization method of basalt fiber dispersion uniformity in rubber composite matrix and its effect on properties - Donglin Zhu; Shaoming Li; Yukun zhou; Hui Xu; Longyu Wang; Yufei Hong; Chuansheng Wang; Huiguang Bian; Mingchao wang (Polymer Testing)
Filler dispersion is one of the key factors affecting the performance of rubber products. At present, the research on the dispersion and distribution detection of fillers in rubber mainly focuses on carbon black and silica materials, while there are relatively few related studies for fiber materials. This paper proposes a method for detecting and characterizing the uniformity of basalt fibers in rubber composites based on machine vision technology, and establishes a mathematical model for uniformity detection and builds an experimental platform, which realizes the characterization of the uniformity of basalt fibers in rubber. Through experiments to verify the feasibility and rationality of the method, the results show that: the uniformity test results in line with the dispersion of fibers in the blending law, and Payne effect and physical and mechanical properties of the results of the trend is consistent, and uniformity test results of the standard deviation of the mean value of about 0.24, the fluctuation of the data basically able to meet the requirements of industrial use.